The experience economy : work is theatre & every business a stage - Pine, B. Joseph; Gilmore, James H., 1959- (Boston : Harvard Business School Press, 1952)
"You are what you charge for. And if you're competing solely on the basis of price, then you've been commoditized. offering little or no true differentiation. What would your customers truly value? Experiences ... The authors explore how successful companies create experiences that engage customers in an inherently personal way ... It's the value that the experience holds for the individual that determines the worth of the offering and the work of the business"--From publisher description.
Step right up -- Welcome to the experience economy -- Setting the stage -- The show must go on -- Get your act together -- Experiencing less sacrifice -- A refreshing experience -- Work is theatre -- Performing to form -- Now act your part -- The customer is the product -- Finding your role in the world -- Exit, stage right.
Includes bibliographical references (p. 207-230) and index.
Keywords: Product management; Diversification in industry; Customer services